Effect of antiretroviral treatment on the risk of tuberculosis during South Africa's programme expansion. (November 2015) - Bachmann, Max O.; Timmerman, Venessa; Fairall, Lara R.
Abstract : Objective: The objective of this study is to estimate the effectiveness of antiretroviral treatment (ART) in preventing tuberculosis (TB) in HIV-infected people during the first 6 years of ART programme expansion. Design: A cohort study comparing TB risk without ART and after ART initiation. Setting: Public sector HIV programme of the Free State province, South Africa. Participants: Seventy-four thousand and seventy-four HIV-infected people enrolled from 2004 until 2010, of whom 43 898 received ART and 30 176 did not. Intervention: Combination ART. Main outcome measures: Time to first TB diagnosis, adjusted for CD4 + cell count, weight, age, sex, previous TB, district and year, with ART, CD4 + cell count and weight as time-varying covariates and with death as a competing risk. Results: Three thousand eight hundred and fifty-eight first TB episodes occurred during 78 202 person-years at risk with ART and 5669 episodes occurred during 62 801 person-years without ART [incidence rates 4.9 and 9.0 per 100 person-years, crude incidence rate ratio 0.55 (95% confidence interval 0.52–0.57)]. The adjusted subhazard ratio (SHR) of time to first TB episode after starting ART, compared with follow-up without ART, was 0.67 (0.64–0.70). Within CD4 + cell count subgroups (<50, 50–199, 100–199, 200–349 and> 350 cells/μl), the respective SHRs were 0.64 (0.57–0.71), 0.63 (0.57–0.70), 0.66 (0.61–0.72), 0.67 (0.62–0.72), 0.72 (0.63–0.83) and 0.97 (0.60–1.59). Adjusted SHRs for ART decreased with each year of enrolment, from 0.90 (0.77–1.04) in 2004 to 0.54 (0.43–0.67) in 2010. Conclusion: ART was effective in preventing TB in HIV-infected patients with CD4 + cell counts below 350 cells/μl, but less so than previously estimated. Effectiveness increased each year.